«ATYPICAL» PROBLEMS OF URBANISM CLASSIFICATION, CHARACTERISTICS AND APPROACHES TO THE SOLUTION: Array - Habrel, M. (Municipal economy of cities. Series: «Economy science», 2020)
In the urban sphere, the problems become more complicated and there are many violations and errors, so the problem of streamlining the problems of urban planning and substantiation of new methodological tools for solving «atypical» problems is relevant, as classical methods are ineffective. In the article the author solved problems: classification, specification of structure and maintenance of urban problems; substantiation of typological features and selection of «atypical» urban problems; outlining the general algorithm and methods of their solution; checks of orderly methodical tools on urban tasks of Lviv. Existing methods and solutions of urban problems are systematized. The general scientific methods of research include: theoretical (convergence from the abstract to the concrete, the method of formalization, the historical method, the system-structural, the method of studying documents); empirical (method of observation, comparison, field surveys, measurements) and empirical-theoretical (abstraction, analysis, synthesis, logical method, modeling), as well as statistical, historical, sociological and cartographic analysis. The classification and «atypical» problems of urban planning are carried out, the methodical tools of their solution are arranged. Methods and means to increase the efficiency of functioning and development of urban systems are based on the provisions of fuzzy sets and their essence. Thus, the new methods should classify urban problems by input and output indicators and knowledge of the internal structure of the system (processes and behavior). According to the theory of validity, in the first step, data are collected using various methods, denoted by codes, grouped into groups to make them more effective. Classification and characterization of «atypical» tasks, as well as updated methodological tools were tested on the example of Lviv — the principles and ways of reforming and developing its spatial structure. The forecast of the future is based on the genesis and historical ways of development of territories and cities. New ways or elimination of old ones meet at radical reforms, and development is caused not only by historical longevity and change of conditions, but also by new processes and behavior of system. There are ways to solve «atypical» problems: simple, including one direction; more complex covers the main direction and two or three additional subdirections; complex includes one or two main directions and several subdirections. This substantiates the feasibility of permanent city design and updating of urban planning documentation.